Exploring the Influence of Potential Entrepreneurs’ Personality Traits on Small Venture Creation: The Case of Saudi Arabia - Alshebami, Ali Saleh; Seraj, Abdullah Hamoud Ali (Frontiers in Psychology, 2022)
This study examined the impact of selected personality traits – innovativeness, internal locus of control, need for achievement and propensity to take risks – on the entrepreneurial intention of Saudi students (young entrepreneurs). The study sample included 165 students from an applied college affiliated with King Faisal University. The participants completed an online self-administered questionnaire, the data from which were analysed using the partial least squares structural equation modelling (PLS-SEM) method. The findings revealed that the characteristics of innovativeness, internal locus of control and propensity to take risks had a positive relationship with entrepreneurial intention. However, the need for achievement had no relationship with entrepreneurial intention. The study model predicted approximately 25% of the total variance in entrepreneurial intention. It is recommended that in future studies, the sample size should be increased and the scope of the study should be broadened.